2012
DOI: 10.1177/1044207312439102
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Experiences and Decisions of Parents/Guardians

Abstract: Participant direction is a service delivery model in which the consumer of public benefits, or his or her surrogate decision maker, exercises some level of choice and control over the consumer's supports and services. In this case study, the authors examined the decisions and experiences of parents/guardians who directed supports and services for an adult with significant intellectual and developmental disabilities (SIDD). Respondents included the parents/guardian of the adult as well as others in the circle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Poorer outcomes in community participation for adults with IDD result when families are without needed supports (Hewitt & Larson, 2007). Consistent with prior research (Gross, Wallace, Blue-Banning, Summers, & Turnbull, 2012), the parents in this study utilized participant direction to transform the challenge of maintaining quality and consistent DSPs into an asset to facilitate progress toward desired outcomes. Half of the participants employed DSPs who had been with them for at least four years.…”
Section: Parent Involvement In Post-school Experiences 20supporting
confidence: 61%
See 1 more Smart Citation
“…Poorer outcomes in community participation for adults with IDD result when families are without needed supports (Hewitt & Larson, 2007). Consistent with prior research (Gross, Wallace, Blue-Banning, Summers, & Turnbull, 2012), the parents in this study utilized participant direction to transform the challenge of maintaining quality and consistent DSPs into an asset to facilitate progress toward desired outcomes. Half of the participants employed DSPs who had been with them for at least four years.…”
Section: Parent Involvement In Post-school Experiences 20supporting
confidence: 61%
“…Additionally, adult agencies should increase efforts to teach all parents about the option and process of participant direction. Efforts to reduce required paperwork or to better prepare families to complete it would likely reduce the skepticism with which some families approach participant direction (Gross et al, 2012). The families in this study utilized participant direction to maintain quality and consistent DSPs who effectively enacted individualized supports for living inclusive and self-determined lives.…”
Section: Discussionmentioning
confidence: 99%
“…Findings indicated that there is still substantial debate around these issues, and policies range from extremely restricted to extremely flexible, despite research showing that people with significant support needs participate in and benefit from supported decision-making in directing their supports and services (Gross et al, 2012;Neely-Barnes, Graff, Marcenko, & Weber, 2008) and hiring family and friends to provide long-term care (Whitlatch & Feinberg, 2006). These structures represented the various types of support provided by the state or its agent to program participants.…”
Section: Discussionmentioning
confidence: 99%
“…We searched 12 social science library databases for peer-reviewed literature, a scholarly research focused search engine and a clearinghouse for gray literature (i.e., documents not published commercially, such as program manuals, organization reports, position statements, policy briefs). We selected the sources for gray literature to search based on site descriptions and previous research (Gross, Wallace, Blue-Banning, Summers, & Turnbull, 2012). Sample selection.…”
Section: Data Collectionmentioning
confidence: 99%
“…According to these parents, work was not the only way to have meaning in one's life. Second, to support choice and self-determination (Bradley, 2000), families need greater awareness and easier implementation of participant-directed services (Caldwell, 2007;Gross, Wallace, Blue-Banning, Summers, & Turnbull, 2012). The flexibility afforded by this option allowed families to achieve many of the positive outcomes described.…”
Section: Discussionmentioning
confidence: 99%